STUDY OF CLIMATE RESILIENCE ACTION IN THE WATER SECTOR WITH THE APPLICATION AND INNOVATION OF NATURE BASE SOLUTION (NBS) - Widyo Astono; Ernamaiyanti; Margareta M. Sintorini (Universitas Trisakti, 2025)
Clean water is one of the goals of sustainable development or Sustainable Development Goals (SDGs) 2030. The Nature-based Solution (NBS) system can coordinate several systems in urban areas to be integrated with water treatment. This study aims to determine the action plan and innovation in the water sector in the application of NBS. This research is a qualitative study. Primary and secondary data obtained will be analyzed by looking at the substance's depth, diversity, and relevance (content analysis). The research locations are the Riau Islands Province, East Kalimantan Province, and East Nusa Tenggara Province. Substance analysis is applied to analyze interview transcript data with stakeholders and the community. The system features maintained in the water sector are water availability for domestic and economic activities, agriculture, energy, environmental and public health, infrastructure, buildings, and other important assets. The ecosystem components are green and blue spaces, blue and green water, and humans. NBS actions in core activities are the construction and adjustment of rainwater storage media for drought disaster resilience